OsmC and incomplete glycine decarboxylase complex mediate reductive detoxification of peroxides in hydrogenosomes of Trichomonas vaginalis - Nývltová, Eva; Smutná, Tamara; Tachezy, Jan; Hrdý, Ivan (Molecular and biochemical parasitology, 2016)
Osmotically inducible protein (OsmC) and organic hydroperoxide resistance protein (Ohr) are small, thiol-dependent peroxidases that comprise a family of prokaryotic protective proteins central to the defense against deleterious effects of organic hydroperoxides, which are reactive molecules that are formed during interactions between the host immune system and pathogens. Trichomonas vaginalis, a sexually transmitted parasite of humans, possesses OsmC homologues in its hydrogenosomes, anaerobic mitochondrial organelles that harbor enzymes and pathways that are sensitive to oxidative damage. The glycine decarboxylase complex (GDC), which consists of four proteins (i.e., L, H, P and T), is in eukaryotes exclusively mitochondrial enzymatic system that catalyzes oxidative decarboxylation and deamination of glycine. However, trichomonad hydrogenosomes contain only the L and H proteins, whose physiological functions are unknown. Here, we found that the hydrogenosomal L and H proteins constitute a lipoate-dependent redox system that delivers electrons from reduced nicotinamide adenine dinucleotide (NADH) to OsmC for the reductive detoxification of peroxides. Our searches of genome databases revealed that, in addition to prokaryotes, homologues of OsmC/Ohr family proteins with predicted mitochondrial localization are present in various eukaryotic lineages. Therefore, we propose that the novel OsmC-GDC-based redox system may not be limited to T. vaginalis.
Keywords: Metabolic Detoxication, Phase I; Oxidation-Reduction; Peroxidases; peroxid vodíku; Lipoate; Recombinant Proteins; Amino Acid Sequence; Hydrogen Peroxide; vazba proteinů; systém štěpení glycinu; kinetika; peroxidasy; exprese genu; Sequence Alignment; sekvence aminokyselin; Peroxide; mitochondrie; Kinetics; rekombinantní proteiny; klonování DNA; oxidace-redukce; Protozoan Proteins; Sequence Homology, Amino Acid; Glycine decarboxylase complex; sekvenční seřazení; Glycine Decarboxylase Complex; axenická kultura; OsmC; Trichomonas; Cloning, Molecular; fylogeneze; protozoální proteiny; Gene Expression; I. fáze biotransformace; Trichomonas vaginalis; Hydrogenosomes; sekvenční homologie aminokyselin; Phylogeny; Axenic Culture; Mitochondria; Protein Binding; Escherichia coli